INFLUENCERS AND CONTENT MARKETING AS THE MAIN DRIVERS OF PURCHASE DECISIONS AT BAKSO O'BOSS, BENGKULU CITY - Muhammad Riski Minandar; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to identify influencers and content marketing as drivers of consumer purchasing decisions at Bakso O'Boss in Bengkulu City. The study uses a quantitative approach with multiple linear regression methods to analyze data obtained from consumers. The results of the analysis show that partially the influencer variable has a positive and significant influence on purchasing decisions, as evidenced by the value> ttable (2,730>1.73406)and Sig level<alpha0.05 = (0.001 < 0.05). The content marketing variable also has a positive and significant influence on purchasing decisions with a value of> ttable (4.453>1.73406) and Sig<alpha0.05 = (0.012 < 0.05).Simultaneously, influencers and content marketing have a significant effect on purchasing decisions, with a calculated F value (16.304) > F table (3.55) and significance (0.000 < 0.05). This study concludes that collaboration between influencers and effective content marketing strategies can increase product appeal and drive consumer purchasing decisions.